Crotalus durissus terrificus Venom Interferes With Morphological, Functional, and Biochemical Changes in Murine Macrophage - Anselmo Hernández Cruz; Ronaldo Z. Mendonça; Vera L. Petricevich (Hindawi Limited, 2005)
Crotalus durissus terrificus venom (Cdt) is toxic for a variety of eukaryotic cells, especially at high concentrations. However its effects on host immune cells are not well known. The purpose of this study was to determine the effect of Cdt on functional status and the mediators production in peritoneal macrophages. The effects of Cdt were analyzed in vitro and were detected using functional status of macrophages as determined by the H2O2 release, spreading percentage, phagocytic index, vacuole formation, and mediators production. Several functional bioassays were employed: cytotoxicity was determined by taking the lyses percentage and the presence of hydrogen peroxide (H2O2) in macrophages, using the horseradish peroxidase-dependent oxidation of phenol red and nitric oxide (NO) in the supernatants of macrophages by the Griess reaction. The tumor necrosis factor (TNF) activity was detected by measuring its cytotoxic activity on L929 cells, and the production the level of other cytokines was assayed using enzyme-linked immunosorbent assay. In vitro studies revealed that Cdt produced (a) a discrete increase in the release of H2O2 and vacuole formation; (b) a decrease in spreading percentage and in the phagocytic index; and (c) an increment in the mediators production. More pronounced increments of IL-6 and TNF were observed after 24 and 48 hours, respectively. Maximum levels of IFN-γ and NO were observed after 96 hours. Interestingly, levels of all mediators presented a discreet decrease, as the amount of Cdt was increased. In contrast, the IL-10 levels observed for all doses studied here did not alter. The IL-6/IL-10 ratio may possibly reflect the balance of pro- and anti-inflammatory cytokines in macrophages, which may be manifested in the inflammatory status during the envenoming processes. Taken together, these data indicate that Cdt have a differential effect on macrophage activation and that this venom is a potent inhibitor of anti-inflammatory response.